Ulno-carpal instability: conservative treatment - Cantero-Téllez, Raquel (My University, 2023)
Carpal instability can be described as the inability of the wrist to maintain its structural integrity under physiologic movements and load. Several theories have been postulated to explain the interaction between the individual bones of the carpus, and their behaviour under load. The ulnocarpal ligaments (UCL) are a group of three ligaments that originate from the palmar anterior edge of the TFC and insert into the ulnar carpal bones. Carpal stability was first described by Linscheid et al. in 1972 (Linscheid et al., 1972) as being dependent primarily on the articular congruity of joint surfaces and the static stability maintained by intact ligaments. Later, the authors amended this to also include the dynamic stability caused by muscle contractions resulting in a compression of joint surfaces (Linscheid and Dobyns, 2002). Conservative approach for ulna carpal instability included the used of orthosis, reinforce of stabilized muscles and proprioception training. Various authors have recommended hand therapy as a treatment option for patients with Ulnocarpal instability despite the lack of clinical evidence or published trials. Many therapy techniques are still in their infancy, although recent developments in the field of neurophysiology and proprioception are providing therapists with more treatment options. The most frequently described orthosis was a three-points-ofpressure design (Duncan, 1989), adapted to incorporate a dorsally directed pisiform boost and volarly directed counter pressure on the ulna head. Good evidence is emerging for the use of various forms of strengthening and rehabilitation programmes for instability of the knee, shoulder and ankle, but as yet, no clinical trials have been published on their use in ulnocarpal instability or indeed any wrist instability, nevertheless, orthosis, reinforce of stabilized muscles and proprioception training is an option for conservative treatment.
Keywords: Carpo - Lesiones y heridas; Muñecas (Anatomía) - Lesiones y heridas; Wrist instability; Ulnar side pain; Ulnocarpal instability